Natural History of Type II Autosomal Dominant Osteopetrosis: A Single Center Retrospective Study - Wang, Ziyuan; Li, Xiang; Wang, Ya; Fu, Wenzhen; Liu, Yujuan; Zhang, Zhenlin; Wang, Chun (Frontiers in Endocrinology, 2022)
Background: Autosomal dominant osteopetrosis Ⅱ (ADO Ⅱ, MIM166600) is a sclerosing bone disorder caused by CLCN7 mutation. The main clinical characteristics include minor trauma-related fracture and hip osteoarthritis, whereas cranial nerve palsy and bone marrow failure rarely develop. Although it is generally believed that ADO II has a relatively benign course, the natural course of the disease in Chinese patients remains unclear. Materials and methods: Thirty-six patients diagnosed with ADO Ⅱ in Shanghai Jiao Tong University Affiliated Sixth People’s Hospital from 2008 to 2021 were studied retrospectively. Among them, 15 patients were followed for an average of 6.3 years (1-14 years). Results: In this study, minor trauma-related fractures of the limb were the most typical clinical manifestations. Visual loss (1/36) and bone marrow failure (2/36), was rare in this study. The condition of ADO Ⅱ seems to be stable in most patients. There were no correlations between markedly elevated bone mineral density (BMD) and minor trauma-related fractures. In total, 21 diseases causing mutations were detected. Among them, the mutation c.2299C>T (p.Arg767Trp) was the most common (16.67%), and mutation c.937G>A [p.(Glu313Lys)] was associated with severe fractures, haematological defects and cranial palsy. Conclusions: Minor trauma-related fracture is the most typical clinical manifestation of ADO II and always occurs in. The mutation p.Arg767Trp is in general a relatively common variant, while the mutation p.(Glu313Lys) seems to be associated with severe phenotype. In our study, ADO Ⅱ seems to remain stable over time.